Ebû İshâk eş-Şâtıbî’nin (790/1388) Şahsı ve Eserlerinin Künyelerine Dair Bilgiler Üzerine Bir Değerlendirme - Baltaci, Burhan (Dinî araştırmalar, 2005)
Abu Ishaq Ibrahim b. Musa b. Muhammed al-Lakhmi al-Shatibi (d.790/1388) is one of the important muslim thinkers and jurists (faqih). This study contains confusions about Abu Ishaq Shatibi’s biography and his works (al-Muwafaqat, al-I’tisam...) and the reasons for it